Case Report: Multi-modal motion-assisted memory desensitization and reconsolidation for traumatic grief (3MDR-TG) - Hengst, Sophie M. C.; Nijdam, Mirjam J.; Gasser, Rebecca; Smid, Geert E. (Frontiers in Psychology, 2025)
BackgroundThe loss of a loved one under traumatic circumstances puts bereaved individuals at risk of developing prolonged grief disorder (PGD), (symptoms of) posttraumatic stress disorder (PTSD) and major depressive disorder (MDD), also referred to as traumatic grief. Traumatic grief is often associated with high symptom levels and strong avoidance. Not all patients benefit from standard treatments. Multi-modal Motion-assisted Memory Desensitization and Reconsolidation (3MDR) has shown to be effective in the treatment of treatment-resistant PTSD. The development of a 3MDR protocol specifically for Traumatic Grief protocol (3MDR-TG) enables grief-focused exposure in an immersive, personalized and activating context.ObjectiveTo provide a proof-of-concept of 3MDR-TG for traumatically bereaved individuals with PGD and PTSD.Method3MDR-TG was applied to a bereaved mother after the traumatic loss of her daughter. Qualitative interviews with the patient and the therapists were conducted to determine feasibility and acceptability. Clinician-rated PTSD, PGD and MDD symptoms were assessed at baseline, after 3MDR-TG, and at 16-week follow-up (primary endpoint).ResultsThe patient and therapists experienced the treatment as feasible and acceptable and rated the credibility of the treatment as high. Although some symptoms temporarily increased following exposure sessions, the overall decrease in PTSD, PGD and depressive symptom severity from baseline to primary endpoint (16 weeks follow-up) corresponded with reliable changes for PGD (RCI = −2.74), PTSD (RCI = −3.05) and depression (RCI = −3.05).ConclusionWe observed a clinically relevant and reliable decrease in PTSD, PGD and depressive symptoms over the course of 3MDR-TG. Further studies of 3MDR-TG in patients with traumatic grief are warranted.